Transmittance correlation of porous silicon multilayers used as a chemical sensor platform - Osorio, Edith (2015)
This work presents a system of two optical microcavities made of mesoporous silicon that have been ana-lyzed as a platform for either chemical sensing or biosensing. When a porous microcavity is exposed toan analyte, the effective refractive index of its layers change, and its optical transmittance shifts towardslower wavenumbers. We constructed a device that employs two identical porous silicon microcavities,one of them is allowed to be in contact with the analyte, whereas the other remains unexposed. The trans-mitted intensity of the system results in the integrated product of the transmittances of both multilayers,which can be approximated to the autocorrelation function of the transmittance of the microcavity. Itsvalue depends on the analyte concentration, so it can be used for sensing purposes. This results in a sensorthat requires neither a wavelength-sensitive detector nor a monochromatic source of illumination, andis robust to changes in temperature, because it only depends on the relative changes in the microcavities.The sensor?s response can be optimized by modifying the angular position of the second microcavity. Asensor based on this principle is demonstrated for isopropyl alcohol detection. The minimum concentra-tion change that can be measured is about 30 ppm, which is equivalent to a minimum measurable changeof refractive index of 5 × 10−5